Response of Long-Term Memory to Molecular Changes of BDNF in Hippocampus in Various Intensities of Physical Activity - Lubis, Leonardo; Setiawan, Setiawan (International Journal of Integrated Health Sciences, 2016)
Objective: To analyze the physiological response of long-term memory (LTM) to the molecular changes of brain-derived neurotrophic factor (BDNF) in the hippocampus by the treatment of various intensities of physical activity. Methods: Subjects were 7–8 week old male Wistar rats weighed between 201–250 grams. This study was an experimental study with pre-(day-1) and post-(day-14) design. Molecular changes reflected by the changes in the expression of mRNA and protein of BDNF in the hippocampus. Treatment of physical activity on the subjects was running on the Animal Treadmill by grouping of the physical activity: light intensity at a speed of 10 m/min, moderate intensity at a speed of 20 m/min and heavy intensity at a speed of 30 m/min. The treatment’s duration was 30 minutes.Then, analysis of data on pre (day-1) and post (day-14) which were: LTM response based on travel time swimming test, the expression of mRNA (Ct) and protein (%) of BDNF in hippocampus based on RT-PCR and immunohistochemistry. Results: The results showed that moderate intensity group caused the better physiological and molecular responses than the other groups, as follows: travel time (0.6260 vs 0.7270 vs 0.9400 vs. 1.4000 seconds (p<0.05)), mRNA BDNF expression (17.2320 vs 18.8800 vs 19.7540 vs 20.7750 Ct (p<0.05)), and hippocampal BDNF protein expression. Conclusions: The study conclude that the moderate intensity is the best physical activity to improve LTM as showed by the BDNF mRNA expression as well as BDNF protein in hippocampus. Keywords: Intensity, long-term memory, brain-derived neurotrophic factor, hippocampus DOI: 10.15850/ijihs.v4n2.839